(Y, Tb, Eu)2O3 monospheres for highly fluorescent films and transparent hybrid films with color tunable emission1. Issue 45 (20th May 2015) - Zhu, Qi; Xiong, Mei; Li, Ji-Guang; Liu, Weigang; Wang, Zhihao; Li, Xiaodong; Sun, Xudong
<x xml:space="preserve">Abstract</x> (Y, Tb, Eu)2O3 monospheres were employed as building blocks for highly fluorescent films and as dispersion fillers for transparent polymer films.